Kreativitas Dan Inovasi Guru Dalam Pembelajaran Berbasis Digital Dengan Media Kelas Virtual Tv Sekolah Pada Anak Usia Dini Di Paud Cinta Kasih Ibu - Tutin Rahayu; Sri Watini; Hotijah; Entri Mardiyanti; Annisa Hakim (Syntax Idea)
Teacher creativity and innovation in the context of digital-based education have become essential topics in efforts to improve educational development in the information technology era. This research examines the role of teacher creativity and innovation in improving digital-based development through the implementation of virtual TV School classroom guidance in several early childhood education institutions, including PAUD Cinta Kasih Ibu Timur Cengkareng West Jakarta, RA Baitul Maal, Jln Pesantren No.62B Jurang Mangu Timur South Tangerang, RA Darul Hikmah Taman Permata Indah II Blok D - RT 11 RW 14 Pejagalan Penjaringan North Jakarta, and Integrated Islamic Kindergarten Padang Kemangi Natuna. The research uses qualitative methods through observation, interviews, and documentation to collect data from several teachers who have actively used virtual classes as an educational tool. This research shows that teachers' efforts to improve the quality of education through creativity and innovation in virtual classroom guidance can significantly impact the development of effective and digital-based education for students.